2017
DOI: 10.1177/0961203317736144
|View full text |Cite
|
Sign up to set email alerts
|

The involvement of galectin-3 in skin injury in systemic lupus erythematosus patients

Abstract: Objective Our previous research suggested that anti-galectin-3 antibody was highly associated with the development of lupus skin lesions in systemic lupus erythematosus (SLE). In this study we aimed to investigate the involvement of galectin-3 in SLE skin damage. Methods The study consisted of 49 patients with SLE, 16 with dermatomyositis and 11 with systemic scleroderma and 20 healthy controls. Galectin-3 was examined by ELISA and immunohistochemical staining in serum and skin, respectively. Results Serum gal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 19 publications
2
16
0
Order By: Relevance
“…Interestingly, in the present study we found that in patients with SLE there was no difference in Gal-3 concentration in groups with and without LE-specific skin lesions. Similar results were obtained by Shi et al in 2018 [9]. It is noteworthy that in the present study we noted for the first time that patients with SLE with and without skin lesions did not differ in G3BP levels.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Interestingly, in the present study we found that in patients with SLE there was no difference in Gal-3 concentration in groups with and without LE-specific skin lesions. Similar results were obtained by Shi et al in 2018 [9]. It is noteworthy that in the present study we noted for the first time that patients with SLE with and without skin lesions did not differ in G3BP levels.…”
Section: Discussionsupporting
confidence: 93%
“…Clinical and laboratory characteristics of patients with systemic lupus erythematosus with lupus-specific skin lesions, systemic lupus erythematosus without lupus-specific skin lesions and discoid lupus erythematosus (NA -not available). P-value in one row shows statistical differences between 2 or 3 values depending on characteristic down resulted in the overexpression of chemokines such as CXCL1 and CCL20, and enhanced the peripheral blood mononuclear cell-attracting capacity of keratinocytes [9]. It is worth mentioning that purified anti-Gal-3 antibodies administered subcutaneously to mice resulted in LE histopathological changes (vasculitis and epidermal atrophy) [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the correlation between galectin‐3 and the pathogenesis of autoimmune diseases has been demonstrated . Moreover, 2 studies showed that galectin‐3 may be correlated with complement 3 and 4 levels and anti‐double‐stranded DNA (anti‐dsDNA) in SLE . In addition, a recent study showed that the pathogenesis of SLE‐related skin injuries may be closely related to anti‐galectin‐3 antibodies, but evidence of the association between clinical manifestations of SLE and galectin‐3 remains limited.…”
Section: Introductionmentioning
confidence: 99%
“…may be correlated with complement 3 and 4 levels and anti-doublestranded DNA (anti-dsDNA) in SLE. 8,9 In addition, a recent study showed that the pathogenesis of SLE-related skin injuries may be closely related to anti-galectin-3 antibodies, 10 but evidence of the association between clinical manifestations of SLE and galectin-3 remains limited.…”
mentioning
confidence: 99%